CRISPR–Cas9-mediated promoter editing of FERONIA-Like receptor 13 increases plant growth and disease resistance in rice - Yanan Guo; Yinyao Qi; Kai Liu; Xiao Luo; Weiyu Xiao; Xiaonan Qiang; Junjie Xing; Feng Yu; Zhenghong Zhao; Long Wang; Lifeng Wang (Crop Journal)
Receptor kinases play a pivotal role in detecting environmental signals, and consequently, gene pleiotropy is frequently observed within this family. However, the trade-off in trait expression resulting from gene pleiotropy poses a constraint on the utilization of such genes in agricultural breeding. In this study, we identified the receptor kinase gene FERONIA-Like Receptor 13 (FLR13) as a pleiotropic gene influencing plant height, tillering, grain yield, and disease resistance. Using promoter editing, we generated novel alleles (FLR13T5T6-1, FLR13T5T6-2) that confer resistance to rice blast and increase per-plant yield. The knockout of the T5T6 segment alleviates the inhibitory effects of two transcription factors, OsGBP1 and OsWRKY53, on FLR13 expression. In summary, our study presents a promising avenue for enhancing the pivotal attributes of receptor-like kinases through a promoter-editing strategy.